Biotic and abiotic drivers of evolution in some Australian thornbills (Passeriformes: Acanthiza) in allopatry, sympatry, and parapatry including a case of character displacement. (13th January 2020) - Coman, Amelia; Potter, Sally; Moritz, Craig; Campbell, Catriona D.; Joseph, Leo
Abstract: Disentangling historical, ecological, and abiotic drivers of diversity among closely related species can benefit from morphological diversity being placed in a phylogenetic context. It can also be aided when the species are variously in allopatry, parapatry, and sympatry. We studied a clade of Australian thornbills (Passeriformes: Acanthizidae: Acanthiza ) comprising the Brown Thornbill ( A. pusilla ), Inland Thornbill ( A. apicalis ), Mountain Thornbill ( A. katherina ), and Tasmanian Thornbill ( A. ewingii ) whose distributions and ecology facilitate this approach. We first clarified phylogenetic relationships among them and then detected a low level of gene flow in parapatry between a non‐sister pair (Brown, Inland). Further work could partition relative roles of past and current hybridization. We identify likely cases of ecologically driven divergent selection and one of convergent evolution. Divergent selection was likely key to divergence of Inland Thornbills from the Brown–Mountain sister pair. In contrast, convergence in plumage between the non‐sister Brown and Inland Thornbills has been driven by their mesic forest habitats on opposite sides of the Australian continent. Finally, morphological distinctiveness of Tasmanian populations of Brown Thornbills could reflect character displacement in sympatry with the ecologically similar Tasmanian Thornbills. Collectively, the combined morphological, genetic, and ecological evidence points to diverse evolutionary processes operating across this closely related group of birds. Abstract : Distribution map of the four species comprising a clade of Acanthiza thornbills studied in the accompanying paper, "Biotic and abiotic drivers of evolution in some Australian thornbills (Passeriformes: Acanthiza ) in allopatry, sympatry, and parapatry including a case of character displacement, " by Amelia Coman, Sally Potter, Craig Moritz, Catriona D. Campbell, and Leo Joseph. The paper presents a case for character displacement in two broadly sympatric species in Tasmania, the Brown Thornbill A. pusilla, and the Tasmanian Thornbill A. ewingii .